Gentiopicroside improves DSS-induced ulcerative colitis and secondary liver injury in mice by enhancing the intestinal barrier and regulating the gut microbiome - Cao, Liu; Niu, Mengyuan; Tang, Xiaoqing; Wang, Yiting; Hu, Xianjing; Dai, Weibo (Scientific reports, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease frequently accompanied by intestinal barrier dysfunction and gut microbiome dysbiosis. Emerging evidence suggests that these impairments can contribute to secondary liver injury (SLI) by disrupting the gut–liver axis and promoting hepatic inflammation. Gentiopicroside (GPS), a natural iridoid glycoside, possesses antimicrobial, anti-inflammatory, and hepatoprotective properties. This study aimed to evaluate the protective effects and underlying mechanisms of GPS in a dextran sulfate sodium (DSS)-induced mouse model of UC and associated SLI. Mice were evaluated for body weight, Disease Activity Index (DAI), colon length, histopathology, tight junction protein expression, gut microbiota composition, inflammatory cytokine levels, and liver function biomarkers. GPS significantly alleviated weight loss, reduced DAI scores, restored intestinal tight junction protein expression, and improved colonic permeability. GPS also modulated the gut microbiota, notably increasing beneficial Bacteroides and Clostridium cluster IV. Mechanistically, GPS suppressed colonic and hepatic inflammation by inhibiting the TLR4/MyD88/NF-κB and JAK2/STAT3 signaling pathways. Moreover, GPS improved liver function and reduced hepatic inflammatory markers, indicating mitigation of SLI. In conclusion, GPS exerts protective effects against DSS-induced UC and SLI by enhancing intestinal barrier integrity, modulating the gut microbiome, and attenuating inflammation via the gut–liver axis.